Globalisasi Hooliganisme terhadap Suporter Sepak Bola di Indonesia - Firman Hendika; Nuraeni Nuraeni (Jurnal Hubungan Internasional, 2020)
Hooliganism is defined as an act of a group of supporters who embrace rogue and destructive actions by a group of football supporters (hooligans), such as fighting, vandalism, and carrying out acts of intimidation. In Indonesia itself, lately the act of hooliganism is rife found through the actions of supporters of football clubs in Indonesia that characterize the actions of British hooligans. Many football supporter groups in Indonesia are starting to follow the style of British hooligans. Supporters from Indonesia get influence and information about hooliganism through social and electronics media that are supported by the entry of globalization era. In this study focuses on how the globalization of hooliganism towards supporters of football clubs in Indonesia which then aims to provide an overview of the development of hooliganism culture in football supporters in Indonesia.In conducting this research, researchers used a qualitative approach with descriptive methods. The data analyzed are the results of literature studies and expert interviews that are relevant to the research that researchers do.The results show that globalization has accelerated the spread of Hooliganism culture towards football supporters in Indonesia. Many groups of supporters in Indonesia feel more powerful when identifying themselves as a hooligan. Naughty and criminal acts are considered as something that must be done to strengthen the existence of their group among other groups.Keywoord: Hooliganism, Globalization, Culture, Media Hooliganisme didefinisikan sebagai suatu tindakan kelompok suporter yang melukan tindakan nakal dan merusak oleh kelompok suporter sepakbola (hooligan), seperti berkelahi, vandalisme, dan melakukan tindakan intimidasi. Di Indonesia sendiri, belakangan tindakan Hooliganisme marak ditemukan melaui tindakan-tindakan para suporter klub sepak bola di Indoensia yang mencirikan tindakan para hooligan asal Inggris. Banyak kelompok suporter sepak bola di Indonesia yang mulai mengikuti gaya para hooligan asal Inggris. Para suporter asal Indonesia mendapatkan pengaruh dan informasi mengenai hooliganisme melalui media sosial dan elektronik yang didukung dengan masuknya era globalisasi. Dalam artikel ini berfokus pada bagaimana globalisasi hooliganisme terhadap kelompok suporter klub sepak bola di Indonesia yang kemudian tujuannya memberikan gambaran mengenai perkembangan budaya Hooliganisme dalam suporter sepak bola di Indonesia.Dalam mengerjakan artikel ini, penulis menggunakan pendekatan kualitatif dengan metode deskriptif. Data yang dianalisis adalah hasil studi literatur serta wawancara para ahli yang relevan dengan artikel yang penulis lakukan.Hasil artikel menunjukkan bahwa dengan adanya globalisasi telah mempercepat penyebaran paham budaya hooliganisme terhadap kelompok suporter sepak bola di Indonesia. Banyak kelompok supoter di Indonesia yang merasa lebih keren ketika meidentifikasikan diri mereka sebagai seorang hooligan. Tindakan-tindakan nakal dan kriminal dianggap sebagai suatu hal yang harus dilakukan untuk memperkuat eksistensi kelompok mereka diantara kelompok lainnya.Kata-Kata Kunci: Hooliganisme, Globalisasi, Budaya, Media